Wastelands : the new apocalypse - Adams, John Joseph, 1976- (Titan Books, 2020)
"Whether the end comes via nuclear war, pandemic, climate change, or cosmological disaster, these stories explore the extraordinary trials and tribulations of those who survive."--Back cover